Role of Contact and Contact Modification on Photo-response in a Charge Transfer Complex Single Nanowire Device - Basori, Rabaya; Raychaudhuri, A. K. (Nano-Micro Letters, 2014)
We investigated the feasibility of obtaining large photoresponse in metal-semiconductor-metal (MSM)type single nanowire device where one contact can be blocking type. We showed that suitable modification of the blocking contact by deposition of a capping metal using focused electron beam (FEB) can lead to considerable enhancement of the photoresponse. The work was done in a single Cu:TCNQ nanowire device fabricated by direct growth of nanowires (NW) from pre-patterned Cu electrode which makes the contact ohmic with the other contact made from Au. Analysis of the data shows that the large photoresponse of the devices arises predominantly due to reduction of the barriers at the Au/NW blocking contact on illumination. This is caused by the diffusion of the photo generated carriers from the nanowires to the contact region. When the barrier height is further reduced by treating the contact with FEB deposited Pt, this results in a large enhancement in the device photoresponse.